2007
DOI: 10.3382/ps.2007-00079
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Phytases on Egg Production and Nutrient Digestibility in Layers Fed Reduced Phosphorus Diets

Abstract: The effects of phytases on the performance of layers and the ileal nutrient digestibility of corn-, soybean-, and by-product meal-based diets were assessed with 320 Hy-Line brown layers from 23 to 28 wk of age. Layers were grouped randomly into 5 treatments, with 8 replicates per treatment and 8 layers per replicate. The 5 diets consisted of a positive control diet with adequate Ca (3.30%), total P (0.50%), and nonphytate P (NPP; 0.28%), and a negative control diet with Ca reduced by 0.12%, total P reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 40 publications
13
41
1
Order By: Relevance
“…The phytase was effective even at the lowest concentration, which shows that the effect was not dose-dependent. It is in agreement with other researchers, who also obtained significantly lower egg production in P deficient treatments (Boling et al, 2000;Augspurger et al, 2007;Liu et al, 2007).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The phytase was effective even at the lowest concentration, which shows that the effect was not dose-dependent. It is in agreement with other researchers, who also obtained significantly lower egg production in P deficient treatments (Boling et al, 2000;Augspurger et al, 2007;Liu et al, 2007).…”
Section: Resultssupporting
confidence: 94%
“…Phosphorus deficiency in laying hens is known to reduce feed consumption. In experiments of some authors (Jeroch and Peter, 1994;Augspurger et al, 2007;Liu et al, 2007) a significant decrease in feed intake in hens fed diets based on maize as a grain source that were not supplemented with dietary phytase was obtained, in case the NPP content ranged from 1.0 to 1.5 g/kg and it was substantially lower than recommended by the NRC (1994). Different results were reported by Vogt (1992) who demonstrated that a maize-soyabean diet containing only 1.2 g NPP/kg had no negative influence on feed intake in layers.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Sunflower meal is rich in fiber and phytic acid, and therefore, a positive effect with the addition of the enzyme complex in the diets was expected; however, no such effect was verified in the present experiment. Liu et al (2007) and Viana et al (2009) also verified that the addition of phytase to diets with reduced nutrient levels did not improve egg production, egg weight, or feed conversion per dozen eggs of layers. The results of these authors were very similar to those found in the present study, where no influence of enzyme complex on those parameters were detected.…”
Section: Sunflower Meal and Supplementation Of An Enzyme Complex In Lmentioning
confidence: 78%
“…The confirmation that stated dietary phytate inhibits sugar digestion and blood glucose in rats (Dilworth et al, 2004) and mice (Lee et al, 2006) resulted in this assumption that anti-nutritional factors capable of altering nutrient utilization might regulate associated gene expression (Liu et al, 2008b). Many studies have shown the effectiveness of phytase supplementation to improve the digestibility of phytate-bound P in poultry diets as well as reducing P excretion (Tangendjaja, Chung, & Broz, 2002) Several experiments have reported the efficacy of microbial phytase in laying hens and broilers diet (Mathlouthi, Larbier, Mohamed, & Lessire, 2002;Panda, Rao, Raju, & Bhanja, 2005;Cowieson & Ravindran, 2007;Liu et al, 2007;Liu et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%